2015
DOI: 10.1063/1.4919602
|View full text |Cite
|
Sign up to set email alerts
|

The temperature-dependent diffusion coefficient of helium in zirconium carbide studied with first-principles calculations

Abstract: The temperature-dependent diffusion coefficient of interstitial helium in zirconium carbide (ZrC) matrix is calculated based on the transition state theory. The microscopic parameters in the activation energy and prefactor are obtained from first-principles total energy and phonon frequency calculations including the all atoms. The obtained activation energy is 0.78 eV, consistent with experimental value. Besides, we evaluated the influence of C and Zr vacancies as the perturbation on helium diffusion, and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…It can obviously be observed that there is a linear relationship between and . This indicates that the obtained diffusion coefficients follow the Arrhenius equation, which is similar to other research results [ 62 , 63 ] rather than meeting that from Equation (15). The slope corresponds to the negative of the macroscopic migration energy barrier .…”
Section: Results Of Dft and Kmc Calculationssupporting
confidence: 91%
See 1 more Smart Citation
“…It can obviously be observed that there is a linear relationship between and . This indicates that the obtained diffusion coefficients follow the Arrhenius equation, which is similar to other research results [ 62 , 63 ] rather than meeting that from Equation (15). The slope corresponds to the negative of the macroscopic migration energy barrier .…”
Section: Results Of Dft and Kmc Calculationssupporting
confidence: 91%
“…Generally, according to the Arrhenius law the diffusion coefficient as a function of temperature is estimated as: [ 62 , 63 ] …”
Section: Results Of Dft and Kmc Calculationsmentioning
confidence: 99%
“…, as shown in Fig.11(b). It indicates that the temperature dependence of D Li could be described by the Arrhenius law[63,64], 𝐷 Li (𝑇) = 𝐷 0 exp (−𝐸 A /𝑘 B 𝑇).…”
mentioning
confidence: 99%
“…By definition, a transition state is characterized by the occurrence of one negative eigenvalue of the dynamical matrix. 3,28 The negative frequencies at −719.45 THz, −173.78 THz and −625.05 THz thus correspond to the transition stats along the BT → BT, BO → BT and BO → BO paths, respectively. Here the doublet modes at the positive frequencies correspond to the vibration of the helium atom perpendicular to the diffusion path, while the singlet mode at the imaginary frequency corresponds to the motion of the helium atom along the diffusion path.…”
Section: B Migration Energy Barriers Of Helium In α-Be Crystalmentioning
confidence: 99%
“…Due to the existence of vacancies or dislocations in the real crystal, the diffusion coefficients will be reduced to a great degree, as investigated in ZrC matrix. 34,35 The formation of helium bubbles would also enhance the probability of helum trapping. To this end, we have made a relevant test to elaborate the effects of the clustering behavior of two helium atoms which can be regarded as the first step to form the helium bubbles.…”
Section: Diffusion Coefficientsmentioning
confidence: 99%